TREATMENT STRATEGIES FOR ALZHEIMER’S DISEASE: A SYSTEMATIC REVIEW OF PHARMACOLOGICAL AND NON-PHARMACOLOGICAL INTERVENTIONS - Oliwia Malec; Maciej Karwat; Mateusz Myśliwiec; Tytus Tyralik; Julia Kular; Justyna Niebylecka; Izabella Michalska; Natalia Glanc; Grzegorz Zalewski; Dominik Sendecki (International Journal of Innovative Technologies in Social Science, 2025)
Background: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder and the leading cause of dementia worldwide, characterized by cognitive decline and functional impairment. Current treatment strategies aim to alleviate symptoms, slow progression and enhance quality of life.Objective: This systematic review aims to critically evaluate the efficacy and safety of pharmacological and non-pharmacological interventions across different stages of Alzheimer’s disease, integrating evidence from randomized controlled trials, high-quality systematic reviews and meta-analyses.Methods: This review followed PRISMA guidelines. PubMed and Google Scholar were searched for English-language studies on pharmacological or non-pharmacological interventions in Alzheimer’s disease. Eligible studies used rigorous designs and reported cognitive, functional, or behavioral outcomes. Two reviewers screened and extracted data independently. Ethical compliance and methodological quality were noted. Due to study heterogeneity, findings were narratively synthesized. A total of 32 studies were included.Results: Pharmacological treatments, particularly cholinesterase inhibitors (rivastigmine, galantamine, donepezil) and NMDA receptor antagonist (memantine), provided modest symptomatic benefits. Emerging monoclonal antibodies targeting amyloid-β (lecanemab, donanemab, aducanumab) showed promise in modifying disease progression. Non-pharmacological interventions, including aerobic exercise, neuromodulation, dietary strategies and music therapy demonstrated potential to improve cognitive, functional, and behavioral outcomes, especially in early-stage AD.Conclusion: Management of Alzheimer’s disease is increasingly shifting toward a comprehensive, multimodal approach. Combining symptomatic therapies with disease-modifying treatments and personalized non-pharmacological approaches offers the most promise for improving patient outcomes. Further research is needed to assess long-term effectiveness and practical implementation of emerging therapies.